Marker-assisted selection complements phenotypic screening at seedling stage to identify cassava mosaic disease-resistant genotypes in African cassava populations - Olasanmi, Bunmi; Kyallo, Martina M.; Yao, Nasser (Springer, 2021)
Cassava mosaic disease (CMD) is a serious threat to cassava production in sub-Saharan Africa. The use of genomic-assisted selection at the seedling trial stage would help to reduce the time for release, breeding cost, and resources used, hence increase selection efficiency in cassava breeding programs. Five cassava populations were screened for resistance to CMD during the seedling evaluation trial at 1, 3, and 5 months after planting using a scale of 1–5. The genotypes in the five populations were also screened using six molecular markers linked to the CMD2 gene. The correlation between the phenotypic and marker data was estimated. Based on Cassava Mosaic Disease Severity Score (CMDSS), between 53 and 82% of the progenies were resistant across the populations with an average of 70.5%. About 70% of the progenies were identified to be resistant to the disease across the populations with a range of 62–80% using the marker data. With both marker data and CMDSS combined, 40–60% of the progenies in each population, with an average of 52%, were identified to be resistant to CMD. There was a fairly significant correlation between the marker data and CMDSS in each cassava population with correlation coefficients ranging from 0.2024 to 0.3460 suggesting that novel genes not associated to the markers used might be involved in the resistance to CMD. The resistant genotypes identified in this study with potential for other desirable traits were selected for evaluation at the advanced trial stage thereby shortening the period required for the breeding program.